Does it Matter Who Pays for Auto Injuries?. Issue 4 (26th February 2018) - Heaton, Paul; Helland, Eric
ABSTRACT: In many states, auto insurers rather than health insurers pay for a substantial fraction of the medical care following auto crashes. We examine whether payer identity affects the care received by auto injury patients. A 2003 Colorado reform shifted a large fraction of auto injury patients from coverage through auto insurers to the traditional health insurance system. Despite negligible changes in auto injury characteristics during this period, treatment supply increased following the reform. Procedure use rose by 5–10 percent and billed charges rose by 5 percent. These changes reflect an increase in resources devoted to treatment, yet do not improve mortality.